Control of the electrophysical characteristics of two-barrier silicon structures with a nanostructured base using gamma radiation - Madatov, R.S.; Abasov, F.P.; Asadov, F.G. (Problems of Atomic Science and Technology, 2023)
During this experimental study, samples of double-barrier structures were irradiated with various doses from a ⁶⁰Co source. The current-voltage characteristics of two-barrier structures from a silicon-based nanostructured base and the change in their spectral photocurrent before and after gamma irradiation were recorded and studied. Experimental results show that voltage values such as open-circuit voltage (Voc) as well as short-circuit current (Isc) and efficiency (η) change with the magnitude of the collection-dissipation voltage. В результаті даного експериментального дослідження зразки двобар’єрних структур опромінювалися різними дозами від джерела ⁶⁰Со. Виміряно та досліджено вольт-ампернi характеристики двобар’єрних структур з наноструктурованою основою на базi кремнію та їх спектральні зміни фотоструму до та після гамма-опромінення. Експериментальні результати показують, що значення напруги, такі як напруга холостого ходу (Voc), струм короткого замикання (Isc) та ефективність (η) залежать від величини напруги накопичення – розряду.